Capital Market Reaction to Announcements the First Case of Coronavirus - Tiara Putri Nadiwa; Irni Yunita (Almana : Jurnal Manajemen dan Bisnis, 2021)
The more important the role of the stock exchange in economic activity, the more sensitive the stock exchange is to various surrounding events, whether they are directly related to economic issues or not. The announcement of the first case of the coronavirus in Indonesia is one of the events that have the potential to affect market behavior. This study aims to analyze the reaction of the capital market to the announcement of the first case of the coronavirus in Indonesia. This study used an event study approach with measurements seen from differences in abnormal returns and trading volume activity before and after the event. The research sample was 45 companies selected by the purposive sampling technique. Data analysis used paired sample t-test on normally distributed data and Wilcoxon test on data not normally distributed. The results showed that there was no difference in abnormal returns and trading volume activity before and after the announcement of the first case of the coronavirus in Indonesia. This study concludes that events do not contain significant information that can influence investors' decisions in the capital market.